Tata kelola media sosial sebagai institusionalisasi praktik akuntansi dalam pengelolaan dana desa di Indonesia - Bambang Arianto (Akuntansi dan Teknologi Informasi, 2023)
This study aims to elaborate on strengthening social media governance as an alternative means of strengthening the principles of transparency and public accountability in managing village funds in Indonesia. Social media has the ability to strengthen the availability of information to the public so as to create the principles of transparency and public accountability for the village fund management process. The availability of information facilities can be an important indicator for the public to participate in supervising village funds so that they are right on target and empower rural communities. This study used an explanatory qualitative approach using in-depth interviews and observation techniques to several rural social media activists in Indonesia. This research finds that social media governance can be an alternative channel to strengthen transparency and public accountability in the management of village funds. However, additional knowledge and competence is needed for village government officials in managing social media. This study also found that strengthening aspects of transparency and accountability through social media is evidence of the institutionalization of accounting practices in managing village funds in Indonesia.